2000
DOI: 10.1084/jem.192.1.137
|View full text |Cite
|
Sign up to set email alerts
|

Taci Is a Traf-Interacting Receptor for Tall-1, a Tumor Necrosis Factor Family Member Involved in B Cell Regulation

Abstract: We and others recently reported tumor necrosis factor (TNF) and apoptosis ligand-related leukocyte-expressed ligand 1 (TALL-1) as a novel member of the TNF ligand family that is functionally involved in B cell proliferation. Transgenic mice overexpressing TALL-1 have severe B cell hyperplasia and lupus-like autoimmune disease. Here, we describe expression cloning of a cell surface receptor for TALL-1 from a human Burkitt's lymphoma RAJI cell library. The cloned receptor is identical to the previously reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
178
2
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(186 citation statements)
references
References 20 publications
4
178
2
2
Order By: Relevance
“…The data were consistent with previous reports (19,22,23) and showed that, over time, the primary anti-NP response was significantly reduced with BAFF inhibition when compared with control animals (Fig. 4).…”
Section: Discussionsupporting
confidence: 82%
“…The data were consistent with previous reports (19,22,23) and showed that, over time, the primary anti-NP response was significantly reduced with BAFF inhibition when compared with control animals (Fig. 4).…”
Section: Discussionsupporting
confidence: 82%
“…3). These data are consistent with previous observations that TRAF3 interacts with TACI, but not BCMA, in mammalian overexpression systems (10,13).…”
Section: Traf3 Is Recruited To Baff-r By Tall-1 Stimulationsupporting
confidence: 83%
“…The R202H mutation is located in the part of the receptor interacting with the calciummodulator and cyclophilin ligand. 26 The binding of APRIL and BAFF induces class switch recombination. 8,9 It is suggested that TACI is involved in the class switch recombination to both IgA and IgG in humans.…”
Section: Discussionmentioning
confidence: 99%